Ameliorative Potential of Chlorogenic Acid on Rotenone-Induced Neurotoxicity in Drosophila Melanogaster Model - Oluwatoyin, Adenike Adeyemo-Salami; Opeyemi, Jamiu Afonja; Olamuyiwa, Faosiyat Adeleke; Adeola, Oluwatosin Adedara; Amos, Olalekan Abolaji (Journal of Public Health International, 2021)
Chlorogenic acid (CA), abundantly found in green coffee beans, is a phenolic compound with antioxidant and anti-inflammatory properties amongst others. Exposure to rotenone, a natural pesticide, induces Parkinsonism (a type of neurodegeneration) through the induction of mitochondria dysfunction and oxidative stress. Phytochemicals with antioxidant properties may be promising in attenuating this condition. In this research, the ameliorative role of CA on rotenone-induced toxicity in Drosophila melanogaster was evaluated. Drosophila melanogaster (Harwich strain, 1- 3 days old) was used. 6 groups of five vials each with 50 flies/vial were exposed to CA (0; control (2% ethanol), 7.5, 15, 30, 45 and 60 mg/kg diet) for 28 days in the longevity analysis. A 28-day survival assay was carried out with rotenone (0, 250 and 500 μM). CA (30 mg/kg diet) was selected to evaluate its ameliorative potential on rotenone. For the study, the flies were divided into four groups of five vials each and exposed to CA and rotenone; Group A- control (2% ethanol), Group B- CA only, Group C- rotenone only and Group D- CA (30 mg/kg diet)+ rotenone (500 μM)for 7 days. Thereafter, the homogenate was evaluated for oxidative stress status, rate of emergence, negative geotaxis and acetyl cholinesterase activity. CA (30 mg/kg diet) extended the lifespan of flies by 21.4%. Also, CA ameliorated rotenone-induced perturbation in catalase, glutathione-S-transferase and acetyl cholinesterase activities, total thiol and glutathione levels, and behavioral deficit (p < 0.05). CA may have ameliorative effect against rotenone-induced toxicity and Parkinsonism.
Keywords: Drosophila melanogaster; chlorogenic acid; rotenone; Parkinson’s disease; oxidative stress; acetyl cholinesterase